Prototype Automatic Maintenance System on Hydroponic Plants Using Fuzzy and Arduino Uno Methods - Fauziah; Gista Nur Mauliddya; Nur Hayati (Institute of Computer Science (IOCS), 2020)
Hydroponic planting media is a planting medium that is currently increasingly popular among the community, with its advantages, namely that it does not require large areas of land because it does not use soil media to plant it but uses water media. Farming using hydroponic techniques has drawbacks, namely the need for persistence to be able to control plant nutrients, water pH, and sufficient water volume so that plants can grow properly. The purpose of this research is how to make a water pH control system, filling water reservoirs, automatic provision Arduino-based nutritional fluids so that it can help facilitate the cultivation process with this hydroponic media. Fuzzy logic helps overcome the intrinsic vagueness of human thinking patterns and natural language, so that it can help understand and respond to unclear human concepts such as heat, cold, big, small, and others. This research begins with the process of designing a tool using Arduino Mega 2560, Logo pH Sensor v1.1, 100 psi DC 12 V 3.5 A pump, and a 12 V DC diaphragm pump, then the process of testing the tool using planting media and yielding a success value of 100% for the water level controller, 80% for the nutrient control, and 75% for the PH control system with an average success value of 85% with the experimental mass for 2 weeks using kale.